2020
DOI: 10.33448/rsd-v9i11.9699
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen and phosphorus dynamics in Nile tilapia farming in excavated rearing ponds

Abstract: The purpose of this study was to determine the total nitrogen (TN) and total phosphorus (TP) balance during intensive tilapia farming in excavated ponds. To quantify TN and TP released into the environment, the supply water, effluents at the harvest time, fish composition, feed, and sediment were analysed. The mass balance between the amount of nutrients that is inserted through the feed, which is transformed into biomass by the fish and is retained in the sediment was calculated based on dry matter. The nutri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 32 publications
0
5
0
2
Order By: Relevance
“…Bernardi et al (2012) highlighted the importance of the hydrographic basin as an environmental management unit, and it is necessary to analyze agricultural activities with modern technological tools such as geotechnologies, as these help obtain technical information that can serve as a decision-making tool for monitoring impacts caused by intensified production. Macedo and Sipaúba-Tavares (2010) affirmed that aquaculture activity causes a nutrients increase in the aquatic environment, increasing the phytoplankton production, leading to changes in the aquatic system, which was confirmed by Coldebella et al (2020). Analyzing the fishery in several fish farms in the western region of Paraná, the results indicated that the concentrations of total solids, chemical oxygen demand (COD), and total phosphorus (TP) increased significantly in the harvest, causing a deterioration of the effluent released into the environment.…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations
“…Bernardi et al (2012) highlighted the importance of the hydrographic basin as an environmental management unit, and it is necessary to analyze agricultural activities with modern technological tools such as geotechnologies, as these help obtain technical information that can serve as a decision-making tool for monitoring impacts caused by intensified production. Macedo and Sipaúba-Tavares (2010) affirmed that aquaculture activity causes a nutrients increase in the aquatic environment, increasing the phytoplankton production, leading to changes in the aquatic system, which was confirmed by Coldebella et al (2020). Analyzing the fishery in several fish farms in the western region of Paraná, the results indicated that the concentrations of total solids, chemical oxygen demand (COD), and total phosphorus (TP) increased significantly in the harvest, causing a deterioration of the effluent released into the environment.…”
Section: Introductionmentioning
confidence: 83%
“…The potential environmental impact of fish activity in the basin was based on a study by Coldebella et al (2020), in which the values of total nitrogen (TN) and TP that remain in the environment and what is discharged into the crop effluent, considering the area of the ponds mapped.…”
Section: Eutrophication Potential Of Fish Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…Among the most important limnological aspects of aquatic life, most notable is the acid-base balance of water, which is directly related to pH and alkalinity (Coldebella et al 2020). Water acidity problems are not the direct result of the effects of low pH, but rather the result of the effects of low total alkalinity and the presence of acidic sediments at the bottom of the ponds (Quispesivana et al 2016).…”
Section: Introductionmentioning
confidence: 99%